PENGARUH PEMAHAMAN RASIONAL PEMBIAYAAN SYARIAH DAN RELIGIUSITAS PETANI TERHADAP SIKAP PETANI DALAM MEMILIH BANK SYARIAH - Broto Judono (University of Merdeka Malang, 2016)
The aim of this study is to analysis the influence of the rational understanding of Islamic financing and the religiosity of farmers on the attitude of farmers in choosing Islamic Banks (Bank Syariah). This data sources are muslim farmers in Rogojampi Banyuwangi. The number of samples are 36 farmers. The result of this research shows that the attitudes of farmers in choosing Islamic Banks directly affected by the rational understanding of Islamic financing. Motive of business profit underlies the farmers to understand financing in Islamic Banks. Religiosity factors dont directly affect the attitude of farmers in choosing Islamic Banks.